188k views
20 votes
3x − 2y = 18
y = 2x − 13

User Faiza
by
4.9k points

2 Answers

2 votes

I'm guessing you want x and y solved.

Answer: x=10 and y=6

Explanation:

For X: Substitute the y-equation (y-2x-13) into the first equation (3x-2y=18) so your equation is 3x-2(2x-13)=18. Do the distribution property and the equation will be 3x-4x+26=18. Put like terms on the same side of the equal sign and combine like terms (subtract 26 on both sides) and the equation will be -x = -10. To make x positive, make both sides positive and you get x=10.

For Y: Substitute your x answer (10) into the first equation (3x-2y=18) and you will get 30-2y=18. Subtract 30 from both sides and you get -2y=12. Divide both sides by the common factor of -2 and you get y=6.

User Jethro
by
5.4k points
13 votes

Answer:

x = - 8

3x - 2y = 18 is the same as 3x - (2x - 13 times 2) = 18

Then I used an algebra site for the rest.

It should be x = - 8

User Shreeya Chhatrala
by
5.2k points